TIBBIY TA’LIMDA GENDER TENGLIK MASALALARINING O‘ZIGA XOS JIHATLARI - Ortiqova, N.M. (SCIENCE and SOCIETY, 2024)
In this article, the issue of continuing the policy of ensuring gender equality is emphasized in medical education, increasing the socio-political activity of women, implementing reforms in their support, creating an atmosphere of intolerance towards harassment and violence against women in society.